Modelling and simulation of the urban rail transit operation system based on system dynamics. (25th April 2022) - Xue, Liang; Zhao, Shengchuan; Li, Jingyao
Based on theories of systems engineering, the present study analyses the correlations between the variables in the urban rail transit operation system, and constructs a system dynamics model for the system. With the historical data of the urban rail transit system in Chengdu City, Sichuan Province in China as the basis, this study adjusts the variables of the four subsystems in the urban rail transit network, and simulates three urban rail transit policy scenarios on the proposed model to estimate the dynamic changes in the major indicators for the operation of the urban rail transit network. The simulation result reveals that adopting different policies according to the development stages of the urban rail transit network can improve the contribution of urban rail transit services to improvement of urban transportation, enhance the performance and maximise social benefits of urban rail transit operators.